Answer:
x=0; x=1
Explanation:
The system presents a quadratic equation and a linear equation. Therefore, the result will have two solutions.
The first step is to match the two equations:
[tex]1+x=1-x^{2}[/tex]
Then we clear the equation by zeroing.
[tex]0=x^{2} +x+1-1[/tex]
Now we perform indicated operations
[tex]x^{2} +x=0[/tex]
We factor with the common factor method
x(x+1)=0
We equal each factor to zero and get the results
x=0
(x+1)=0
x=-1
The two values that satisfy both equations are 0 and -1